2019
DOI: 10.3390/v11050430
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 Uncoating Occurs in the Cytoplasm without Capsid Disassembly and It Is Facilitated by Depletion of Capsid-Associated Divalent Cations

Abstract: Human parvovirus B19 (B19V) traffics to the cell nucleus where it delivers the genome for replication. The intracellular compartment where uncoating takes place, the required capsid structural rearrangements and the cellular factors involved remain unknown. We explored conditions that trigger uncoating in vitro and found that prolonged exposure of capsids to chelating agents or to buffers with chelating properties induced a structural rearrangement at 4 °C resulting in capsids with lower density. These lighter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…4B). In a recent study, we showed that a large proportion of B19V particles accumulating in the nuclear fraction of the infected cells have the viral DNA accessible and therefore are sensitive to nuclease digestion (26). As shown in Fig.…”
Section: Generation Of B3galnt1 Ko Ut7/epo Cell Linementioning
confidence: 82%
See 1 more Smart Citation
“…4B). In a recent study, we showed that a large proportion of B19V particles accumulating in the nuclear fraction of the infected cells have the viral DNA accessible and therefore are sensitive to nuclease digestion (26). As shown in Fig.…”
Section: Generation Of B3galnt1 Ko Ut7/epo Cell Linementioning
confidence: 82%
“…After three washes with PBS, the cells were resuspended in 500 l MEM containing 5% FCS and 2 U/ml EPO and incubated at 37°C. After 3 h, cells were pelleted and washed thrice with PBS, and the nuclei were extracted using the Nuclei EZ Prep kit (Sigma-Aldrich, MO), as previously described (26). Trypan blue staining was used to evaluate the integrity of the isolated nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, a recent study on another non enveloped virus, Parvovirus B19, pointed to the involvement of dynein in the transport of virus particles released from endosomes into the proximity of the nucleopore and, also, in the induction of conformation changes in virus particles occurring in the cytosol (facilitated by the depletion of capsid-associated divalent cations). The changes in conformation resulted in partial exposure of the genomic DNA prior to particle translocation to the nucleus [89].…”
Section: Involvement Of Microtubules and Microtubule Motors In Pyv Trmentioning
confidence: 99%
“…However, even a transient binding of a capsid to globoside can trigger conformational modifications leading to exposure of the VP1u region [12], allowing interaction of its N-terminal region with a specific, but yet uncharacterized receptor whose distribution in cells of erythroid lineage matches the susceptibility of cells to productive infection [13,14,15]. Following binding, internalization via clathrin-mediated endocytosis can occur, the phospholipase activity associated to the VP1u region consents escape from the endosome, and by subsequent coordinated intracellular transport and uncoating events, a single-stranded genome is finally delivered in the nuclear environment [16,17].…”
Section: The Lifecyclementioning
confidence: 99%